Application of Content Marketing in Building Brand Awareness on Instagram - Aji Prasojo; Sri Aliami (Universitas 45 Surabaya, 2024)
To reach a broader market, businesses that develop in the digital era require innovation and creativity. Business actors must have an excellent digital marketing strategy to promote the goods being sold. Good content marketing to introduce products on social media can increase brand awareness. This research aims to find out how to use content marketing to increase brand awareness of Bakpia Masaji on Instagram. This research uses a descriptive qualitative approach involving interviews and direct observation. The results show that content marketing used to increase brand awareness of Bakpia Masaji on Instagram has a positive effect on customers through informative, exciting and relevant marketing content.